Elliptic Stark conjectures and exceptional weight one forms - Darmon, H; Lauder, A; Rotger, V (Mathematical Sciences Publishers, 2024)
A classical point of the Coleman-Mazur eigencurve is said to be exceptional if the map to weight space is non-´etale at that point. The goal of this paper is to revisit the p-adic elliptic Stark conjecture of [DLR1] concerning a triple (f, g, h) of classical modular forms of weights (2, 1, 1), and extend it to the setting where the p-stabilised eigenform g corresponds to such an exceptional point.